The Effect of Cold Plasma Dry Treatment on the Properties and Structures of Polymerized Peanut Protein Isolate-Inulin - HUI Cai-qin; FU Wen-jie; LAN Hui-hui; LIU Shuo; JI Hui (Liang you shipin ke-ji)
In order to avoid the timeliness of plasma treatment effect, it is necessary to improve the solubility and functional properties of peanut protein and expand the application of peanut protein in food industry. Cold Plasma (CP) was used to induce Peanut Protein isolator-inulin (PPI-Inulin) dry polymerization reaction and study the effects of CP on PPI-Inulin after treatment for 0, 1, 2, 3, 4 and 5 min. Effect of reaction time on the polymerization of PPI and inulin. The results indicated that CP treatment significantly enhanced the solubility and emulsification stability of PPI-Inulin polymer. When the treatment time was 3 min, the maximum solubility of PPI-Inulin polymer was 4.28 mg/mL, which increased by 28.14% compared with the untreated polymer. The effect of CP treatment on the structure of peanut protein isolate was analyzed by measuring its molecular weight, thermal stability and spectral changes. The results showed that after CP treatment, PPI and inulin did not covalently bind, and may be polymerized by non-covalent bond. The relative percentage content of β-folding + random curling decreased, the relative percentage content of α-helix+β-angle increased, the orderly structure of PPI increased, and the structure became tighter.